Dreams and reality: autonomy support for women entrepreneurs in Ethiopia. Issue 7 (16th September 2019) - Hailemariam, Atsede Tesfaye; Kroon, Brigitte; van Engen, Marloes; van Veldhoven, Marc
Abstract : Purpose: Taking a self-determination theory (SDT) perspective, the purpose of this paper is to understand the socio-cultural context on the satisfaction of basic psychological needs for autonomy, competence and relatedness in the entrepreneurial activity of women entrepreneurs in Ethiopia. Design/methodology/approach: Semi-structured in-depth interviews were conducted with 19 women entrepreneurs operating business in the formal sector of the economy in Addis Ababa. A thematic analysis approach was used to analyze and interpret the interview transcripts. Findings: Women entrepreneurs experience autonomy-supportive and controlling socio-cultural contexts in their gender role, parent–daughter relationship, husband–wife relationship and their religious affiliation. Autonomy-supportive social agents provide women entrepreneurs, the chance to perceive themselves as competent and autonomous to exploit and choose opportunities and run their business in accordance with their personal values and interests. On the other hand, controlling social agents maintain and reinforce the existing male-dominated social and economic order. They constrain women's entrepreneurial performance by undermining their basic psychological needs satisfaction, which limits their autonomous functioning and well-being in entrepreneurial activity. Practical implications: To promote women's autonomous functioning and well-being in entrepreneurial activity, policy should be aimed at reducing constraints to the satisfaction of psychological needs for autonomy, competence and relatedness in the socio-cultural context. Originality/value: The study is the first to apply SDT to explore the influence of autonomy vs controlling socio-cultural contexts on satisfaction vs thwarting needs for autonomy, competence and relatedness in the entrepreneurial activity of women.